Association of podoplanin expression to histopathological grades of oral epithelial dysplasia and oral squamous cell carcinoma - Shabir, Hina; Haider Durrani, Sofia; Tariq, Sahibzade Fatima; Salam Khatak, Sana; Saleem Khan, Abbas; Nazir Arbab, Kanwal (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the expression of podoplanin, and to correlate it with histopathological grades in oral epithelial dysplasia and oral squamous cell carcinoma cases. Methods: The retrospective, analytical, cross-sectional study was conducted at the City Laboratory, Peshawar, Pakistan, and comprised specimen block data of histologically diagnosed cases of oral benign lesions, dysplastic lesions and oral squamous cell carcinoma from January 2017 to August 2021. Two sections (4um) were cut from each specimen block for Haematoxylin and Eosin staining and immunohistochemistry. The slides were re-evaluated by two pathologists for confirmation of the diagnosis, and podoplanin marker was applied to cases selected using immunohistochemistry. Data was analysed using SPSS 22. Results: Of the 80 cases identified, 68(85%) were analysed. There were 20(29.4%) benign cases; 11(55%) females and 9(45%) males with mean age 39.90±16.23 years, 20(29.4%) oral dysplastic cases; 14(70%) males and 6(30%) females with mean age 57.75±12.02 years, and 28(41.2%) oral squamous cell carcinoma cases; 17(61%) males and 11(39%) females with mean age 50.55±14.80 years. Podoplanin expression in oral epithelial dysplasia cases was significant (p=0.028), while it was not significant in the other 2 groups (p>0.05). Conclusion: Podoplanin when used along with histopathological evaluation could help in the diagnosis and grading of oral epithelial dysplasia lesions. Key Words: Oral epithelial dysplasia, Oral squamous cell carcinoma, Podoplanin.